Elevation of plasma phenytoin by viloxazine in epileptic patients: a clinically significant drug interaction. Issue 2 (February 1992) - Pisani, F; Fazio, A; Artesi, C; Russo, M; Trio, R; Oteri, G; Perucca, E; Di Perri, R
Abstract : The effect of viloxazine (150-300 mg daily for 21 days) on plasma phenytoin levels at steady state was examined in 10 epileptic patients stabilised on a fixed phenytoin dosage. After starting viloxazine treatment, plasma phenytoin concentrations increased by 37% on average (range 7-94%) from a mean value of 18.8 micrograms/ml at baseline to a mean value of 25.7 micrograms/ml during the last week of combined therapy. In four patients the rise in plasma phenytoin was associated with the development of signs of phenytoin toxicity. Discontinuation of viloxazine resulted in return of plasma phenytoin towards baseline values and disappearance of the clinical symptoms. The mechanism of interaction probably involves inhibition of phenytoin metabolism by viloxazine. Careful monitoring of plasma phenytoin levels is recommended in patients treated with phenytoin who need to be started on viloxazine therapy.